Islam dan Budaya Politik Melayu - Muhammad Abdillah (Medina-te : Jurnal Studi Islam, 2021)
This paper aims to examine the relationship between Islam and the Malay world which has been widely studied by experts and researchers. A special description of the contestation between Islam and Malay political culture as a form of open-minded society, to be able to see how Islamic and Malay political culture is in a simple way. This research departs from the questions: first, how is Islam in Malay history?; second, how is the dynamics of Islam and Malay political culture. In this paper, qualitative methods are used to clearly examine Islamic and Malay political culture. This paper also aims to show that Islam has an integral role in the history of civilization of the Malay world, besides that Islam also has strong credibility in relation to politics from various perspectives, not only from a religious point of view, but also from a scientific point of view. viewpoint. This research uses a descriptive qualitative approach to look at how to find literature data and interpret the data contained in reference sources and various supporting sources about the contribution of Islamic thought in the Malay world.